2020
DOI: 10.3390/cancers12123731
|View full text |Cite
|
Sign up to set email alerts
|

Bruton’s Tyrosine Kinase Inhibitors Ibrutinib and Acalabrutinib Counteract Anthracycline Resistance in Cancer Cells Expressing AKR1C3

Abstract: Over the last few years, aldo-keto reductase family 1 member C3 (AKR1C3) has been associated with the emergence of multidrug resistance (MDR), thereby hindering chemotherapy against cancer. In particular, impaired efficacy of the gold standards of induction therapy in acute myeloid leukaemia (AML) has been correlated with AKR1C3 expression, as this enzyme metabolises several drugs including anthracyclines. Therefore, the development of selective AKR1C3 inhibitors may help to overcome chemoresistance in clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The AKRs do not appear to be involved in resistance to these agents. To the contrary, the tyrosine kinase inhibitor ibrutinib is an inhibitor of AKR1C3 and can counteract anthracycline drug resistance mediated by AKR1C3 (Morell et al, 2020). Apatinib also inhibits the NRF2 pathway which would lead to a downregulation of AKR genes regulated by NRF2 and could surmount drug resistance to other chemotherapeutic agents (Sun et al, 2020).…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…The AKRs do not appear to be involved in resistance to these agents. To the contrary, the tyrosine kinase inhibitor ibrutinib is an inhibitor of AKR1C3 and can counteract anthracycline drug resistance mediated by AKR1C3 (Morell et al, 2020). Apatinib also inhibits the NRF2 pathway which would lead to a downregulation of AKR genes regulated by NRF2 and could surmount drug resistance to other chemotherapeutic agents (Sun et al, 2020).…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…Another study by Eide et al recently reported that the primary AML samples with 11q23 MLL rearrangements are highly sensitive to ibrutinib in combination with the BCL-2 inhibitor venetoclax (63). Furthermore, both ibrutinib and acalabrutinib exhibit synergistic effects with daunorubicin on inducing cytotoxicity in AKR1C3-expressing AML cells via efficiently preventing daunorubicin inactivation mediated by AKR1C3, an enzyme associated with the emergence of multidrug resistance (MDR) (64). Therefore, clinical data from ongoing trials and better understanding of the mechanisms of action for ibrutinib and acalabrutinib will guide the design and improvement of future trials, including optimization of the combination regimens and appropriate patient stratification according to relevant genetic alterations and contexts.…”
Section: Hematological Malignancies Of Myeloid Cells and T Cellsmentioning
confidence: 99%
“…Among the reductases, AKR1C3 is the most active enzyme, with a confirmed role in ANT resistance . Valuable experiments have shown that inhibition of the AKR1C3-catalyzed metabolism of DAU leads to an increase in the efficacy of DAU against cancer cells and sheds light on the possible potential to reverse ANT resistance. In triple-negative breast cancer (TNBC), AKR1C3 expression has been shown to be associated with reduced sensitivity to doxorubicin (DOX) . Upregulation of AKR1C3 expression is thought to be one of the key factors in MCF-7 breast cancer cells resistance to DOX .…”
Section: Introductionmentioning
confidence: 99%